MAIN METHODICAL RECOMMENDATIONS ON THE TEACHING OF GENERAL TECHNICAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the principal methodical recommendations on the construction and of delivering the course of lectures on general engineering science at the University.